EFEKTIVITAS PEMBERIAN AIR REBUSAN JAHE MERAH TERHADAP PENURUNAN DISMENOREA MAHASISWI D-III KEBIDANAN UNIVERSITAS PASIR PENGARAIAN - Wahyuny, Romy; Yuli, Nova; Fitria, Rahmi; Junita, Elvira (Maternity and Neonatal : Jurnal Kebidanan, 2024)
Menstruation is periodic and cyclic bleeding from the uterus, accompanied by uterine shedding and shedding of the endometrium. Menstruation occurs regularly with a cycle every month. The average cycle is between 27-30 days. Dysmenorrhea is a common complaint experienced by young women. Many factors cause dysmenorrhea, namely the menstrual cycle, length of menstruation, body mass index (BMI), age of menarche that is too early or too late, physical activity, and stress. The purpose of this study was to find out whether giving red ginger boiled water was effective in reducing Dysmenorrhea in DIII Midwifery Students at Pasir Pengaraian University. This study used an experimental research design with a pre-experimental research design, with a one group pretest-posttest design approach. The population of this study were female students at D-III Midwifery, Pasir Pengaraian University, with 73 respondents and a sample size of 42 respondents. with the sampling technique used Nonprobability sampling with simple random sampling method. with Bivariate Analysis using the T-dependent test. The results of this study indicate that the average level of Dysmenorrhea before being given red ginger boiled water is 6.50 with a standard deviation of 1.67. the average dysmenorrhea after being given red ginger boiled water was 3.90 with a standard deviation of 1.63. The statistical test results obtained a value of P = 0.00 (p <0.05). this shows that there is effectiveness of giving red ginger boiled water to reduce dysmenorrhea. Keywords : Ginger Boiled Water, Dysmenorrhea, Adolescents